A Therapeutic Microneedle Patch Made from Hair-Derived Keratin for Promoting Hair Regrowth - Yang, Guang; Chen, Qian; Wen, Di; Chen, Zhaowei; Wang, Jinqiang; Chen, Guojun; Wang, Zejun; Zhang, Xudong; Zhang, Yuqi; Hu, Quanyin; Zhang, Liang; Gu, Zhen (ACS nano, 2019)
Activating hair follicle stem cells (HFSCs) to promote hair follicle regrowth holds promise for hair loss therapy, while challenges still remain to develop a scenario that enables enhanced therapeutic efficiency and easy administration. Here we describe a detachable microneedle patch-mediated drug delivery system, mainly made from hair-derived keratin, for sustained delivery of HFSC activators. It was demonstrated that this microneedle device integrated with mesenchymal stem cell (MSC)-derived exosomes and a small molecular drug, UK5099, could enhance the treatment efficiency at a reduced dosage, leading to promoted pigmentation and hair regrowth within 6 days through two rounds of administration in a mouse model. This microneedle-based transdermal drug delivery approach shows augmented efficacy compared to the subcutaneous injection of exosomes and topical administration of UK5099.